2022
DOI: 10.1136/bmjopen-2022-062127
|View full text |Cite
|
Sign up to set email alerts
|

Characterising methamphetamine use to inform health and social policies in Manitoba, Canada: a protocol for a retrospective cohort study using linked administrative data

Abstract: IntroductionRising use of methamphetamine is causing significant public health concern in Canada. The biological and behavioural effects of methamphetamine range from wakefulness, vigour and euphoria to adverse physical health outcomes like myocardial infarction, haemorrhagic stroke, arrhythmia and seizure. It can also cause severe psychological complications such as psychosis. National survey data point to increasing rates of methamphetamine use, as well as increasing ease of access and serious methamphetamin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 51 publications
(71 reference statements)
0
4
0
Order By: Relevance
“…Psychosis is a symptom experienced by many people who use methamphetamine [3,4] and a common indication for inpatient admission. This study attenuates the potential of confounding by indication by surveying a population admitted to hospital, who would have been admitted for psychiatric concerns such as mood or psychotic disorders that may be related to methamphetamine use.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Psychosis is a symptom experienced by many people who use methamphetamine [3,4] and a common indication for inpatient admission. This study attenuates the potential of confounding by indication by surveying a population admitted to hospital, who would have been admitted for psychiatric concerns such as mood or psychotic disorders that may be related to methamphetamine use.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…A recent meta-analysis revealed that 36.5% of people who use methamphetamine develop symptoms of psychosis, a figure far higher than with any other illicit drug [3]. Local data show that Manitobans who used methamphetamine were 43.7 times more likely to be diagnosed with a psychotic disorder within 12 months of their first methamphetamine-related contact with the healthcare system than the general population [4]. It can be difficult to differentiate acute symptoms of psychosis related to methamphetamine use from those related to a chronic primary psychotic disorder [5].…”
Section: Introductionmentioning
confidence: 99%
“…Methamphetamine, a widely used illegal drug, has become a significant public health concern worldwide [ 1 ]. The biological and behavioral effects of methamphetamine range from wakefulness, vigour, and euphoria to adverse outcomes such as myocardial infarction, arrhythmia, haemorrhagic stroke, and psychosis [ 2 , 3 ]. A strong association has been found between methamphetamine abuse and non-lethal haemorrhagic stroke by previous studies [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“… 1 In Canada, the number of Manitobans that received first-time care for methamphetamine use increased from 208 in 2013 to 1,454 in 2018. 10 Moreover, amphetamine-related emergency department (ED) visits in Winnipeg increased from 10 to more than 150 visits between 2013 and 2017. 11 Furthermore, hospitalizations in British Columbia and Alberta doubled from 591 to 1,210 visits, and from 217 to 460 visits, respectively, between 2012 and 2014.…”
Section: Introductionmentioning
confidence: 99%